Asuransi Proteksi Medis (Professional Indemnity Insurance) sebagai Pengalihan Tanggung Gugat dalam Sengketa Medis Dokter-Pasien - Prima Maharani Putri; Gregorius Yoga Panji Asmara (Universitas Muhammadiyah Purwokerto, 2022)
The aims of this article is to analyze the suitability of professional indemnity insurance with applicable laws and regulations in Indonesia, especially in the field of health law and its implications for quality. health care in Indonesia. This research uses normative juridical approaches with statute approach and conceptual approach. Based on the results of the study, Law No. 40 of 2014 on Insurance is the attitude and anticipation of the government to encourage national development, especially in the development of the industry. insurance. The doctor-patient paternalistic relationship, which is now a partnership relationship, is characterized by therapeutic transactions and informed consent in every health service. This is based on the provisions of Law No. 29 of 2004 on Medical Practice and Regulation of the Ministry of Health No. 290 /MenKes/ Per / III /2008 on Approval of Medical Measures. Health services that are